PEMBATASAN HAK UNTUK MENIKAH ANTARA PEKERJA DALAM SATU PERUSAHAAN - Novenanty, Wurianalya Maria (Faculty of Law, Parahyangan Catholic University, 2016)
There are a number of corporations or economic entities which enact internal employment regulations prohibiting its employees to inter-marry. Sanction to the violation of this rule is voluntary or forced resignation. It is argued that the ratio legis is to prevent personal conflict of interest, discriminative treatment and incidence of corruption-collusion and nepotism in the work place. The author shall critically analyze such regulation against the background of the prevailing laws, i.e. the 1945 Constitution, Human Rights laws, Marriage Law (1/1974) and Labor law (13/2003). The author’s main finding is that it is permissible to restrict a person’s right to marry under certain conditions, i.e. in the nation’s interest and public order and that such limitation can only be applied by public corporations working in the public interest. Keywords: human rights, marriage, labor, corporations